Bacimethrin, an allelopathic vitamin B1 antagonist, is linked with microbial gene expression patterns in a hypereutrophic watershed - Kelly C. Shannon; Frederick S. Colwell; Byron C. Crump; Elizabeth Brennan; Gillian St. John; Robin Gould; Christopher Hartzell; McKenzie Wasley; Christie Nichols; Clifford E. Kraft; Christopher P. Suffridge (PLoS ONE, 2025)
Freshwater cyanobacterial harmful algal blooms (cyanoHABs), often dominated by Aphanizomenon , Dolichospermum , and Microcystis, are intensifying in eutrophic watersheds globally. A potential control on bacterioplankton dynamics in these systems is the availability of the essential metabolic cofactor thiamin (vitamin B 1 ) and presence of the allelopathic thiamin antagonist bacimethrin, which causes competitive inhibition of thiamin-requiring enzymes. We examined dissolved concentrations of thiamin chemical congeners and bacimethrin, 16S amplicon-based microbiome compositions, prokaryotic mRNA-based metatranscriptomes, and reference genomes in hypereutrophic Upper Klamath Basin before and during seasonal cyanoHABs. Our objective was to connect bacterioplankton community compositions and gene expression patterns with thiamin congener and bacimethrin availability under different cyanoHAB conditions. Bacimethrin was present in all samples at similar concentrations to the thiamin precursor, HMP, suggesting that similar mechanisms influence the availability of both compounds. Additionally, bacimethrin concentrations were positively correlated with cyanoHAB species abundance (cells mL -1 ) and the expression of microbial thiamin biosynthesis genes. Samples with high cyanoHAB abundance also displayed elevated transcription of genes in key biochemical pathways such as the pentose phosphate pathway, photosynthesis, and glycogen biosynthesis. Bacterioplankton such as Limnohabitans spp. that are unable to synthesize thiamin, and are thus vulnerable to bacimethrin allelopathy, showed reduced gene expression when cyanoHAB abundance was high. Reference genomes of cyanoHAB and many picocyanobacteria strains contained complete thiamin biosynthesis gene pathways, implicating these taxa as major thiamin sources. These results suggest that bacimethrin provides a competitive advantage to bacterioplankton that do not require exogenous thiamin by eliminating the risk of bacimethrin uptake with thiamin transporters, potentially facilitating cyanoHAB dominance in Upper Klamath Basin and broader eutrophic watersheds.